1991
DOI: 10.1099/00221287-137-12-2689
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and genetic characterization of the rfb region from Yersinia pseudotuberculosis serogroup IIA, which determines the formation of the 3,6-dideoxyhexose abequose

Abstract: The rfb region of Yersinia pseudotuberculosis serogroup IIA has been cloned and expression of 0 antigen in Escherichia coli K12 was demonstrated. Transposon mutagenesis analysis confined the DNA region required for 0 antigen expression to a 19.3 kb fragment, and the 0 antigen expressed was visualized by SDS-PAGE and silver staining. Southern hybridization analysis demonstrated significant levels of similarity between the Yersiniu rcfb region and the 3,6-dideoxyhexose pathway genes rfbF and rfbG, previously iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Initiation towards this goal began with the cloning and analysis of the Salmonella typhimurium rfb (0-antigen) cluster, which led to the elucidation of the entire sequence of this region and the identification of 12 of the 15 genes present in the cluster (6,15,46). Subsequently, the deoxy and dideoxy genes within the rfb clusters of S. typhimurium (group B, which contains abequose) were compared to those within Salmonella paratyphi (group A, which contains paratose), Salmonella typhi (group D, which contains tyvelose), and, most recently, Y pseudotuberculosis M85 (serogroup IIA, which contains abequose) (17,18). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation towards this goal began with the cloning and analysis of the Salmonella typhimurium rfb (0-antigen) cluster, which led to the elucidation of the entire sequence of this region and the identification of 12 of the 15 genes present in the cluster (6,15,46). Subsequently, the deoxy and dideoxy genes within the rfb clusters of S. typhimurium (group B, which contains abequose) were compared to those within Salmonella paratyphi (group A, which contains paratose), Salmonella typhi (group D, which contains tyvelose), and, most recently, Y pseudotuberculosis M85 (serogroup IIA, which contains abequose) (17,18). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In Salmonella serogroups A, B and D, the $ 6 gene is located outside the r + region (Collins & Hackett, 1991), while in Salmonella enterica serogroups C1, C2 and El, Sbigella hsenteriae type I, and SbigellafEexneri, $ 6 is located within the r -gene cluster (Brown et a/., 1991 ;Lee e t al., 1992;Wang e t al., 1992;Morona e t al., 1994). In the $6-independent polymerization represented by Escbericbia coli serotypes 0 8 and 0 9 , the 0-antigen is synthesized by processive transfer of sugars to a growing chain attached to undecaprenol pyrophosphate (Jann & Jann, 1984;Whitfield & Valvano, 1993).…”
mentioning
confidence: 99%
“…We have previously reported the cloning of the Y pseudotuberculosis serogroup IIA rib region (19). Hybridization studies of this abequose-producing strain (M85) had shown that at least some of the M85 rib genes are related to DDH pathway genes (rfbF and rCbG) of S. enterica LT2.…”
mentioning
confidence: 99%
“…We have previously reported the cloning of the Y pseudotuberculosis serogroup IIA rib region (19 (51).…”
mentioning
confidence: 99%
See 1 more Smart Citation